Design and realisation of a twin rotor system - Soong, Jin Xian (2016)
Wide application of unmanned aerial vehicle has been attracting a lot of attentions. People all around the world have invested countless effort and time to understand the behaviour of unmanned aerial vehicle in order to maximise its efficiency. However, studying dynamics of unmanned aerial vehicle are usually complex and expensive. In that regard, a solution proposed would be designing a practical ground based experiment setup. This Final Year Report presents a Twin Rotor System model with the application of PIXHAWK and MATLAB Simulink®. Mechanical design on Twin Rotor System experiment setup will be reviewed based on several Basic Design Rules and Embodiment Design Principles. Besides, components involved in the architecture of circuitry for Twin Rotor System experiment setup will also be described in detail. The purpose of designing Twin Rotor System is to establish a data acquisition experiment setup. In this 1 degree of freedom Twin Rotor System experiment setup, control on Roll – angle are interested. System model of Twin Rotor System will be constructed by means of MATLAB Simulink®. PID tuning of Twin Rotor System which gives the most pleasing response are recorded and the appropriateness of Twin Rotor System response will then be evaluated by plotting graphs of angular displacement over time.